2007
DOI: 10.1111/j.1463-1318.2007.01225.x
|View full text |Cite
|
Sign up to set email alerts
|

The impact of surgeon and pathologist on lymph node retrieval in colorectal cancer and its impact on survival for patients with Dukes’ stage B disease

Abstract: Overall lymph node harvest, in this unit, varied according to the reporting pathologist but not operating surgeon. As lymph node harvest increased to 15 per patient, the probability of identifying a metastatic node increased.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
83
5
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(105 citation statements)
references
References 32 publications
15
83
5
2
Order By: Relevance
“…Our results are in total agreement with similar recent studies suggesting that tumor location, tumor grade [13], stage [14][15][16] and size is significantly impacting the number of identifiable LNs [17]. Shen et al have recently reported that number of harvested LNs is most significantly associated with tumor location (right sided vs left sided cancer), patient age and length of resected specimen [12].…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Our results are in total agreement with similar recent studies suggesting that tumor location, tumor grade [13], stage [14][15][16] and size is significantly impacting the number of identifiable LNs [17]. Shen et al have recently reported that number of harvested LNs is most significantly associated with tumor location (right sided vs left sided cancer), patient age and length of resected specimen [12].…”
Section: Discussionsupporting
confidence: 83%
“…This was the most compelling factor when comparing the VAMC to KUMC. Several studies have suggested the potential impact of surgeons training and surgical techniques on lymph node harvesting [14,15,[19][20][21][22][23]. It has been known that surgeons with more training and/or experience in colorectal procedures were more successful in obtaining adequate resections.…”
Section: Discussionmentioning
confidence: 99%
“…Those two modifiable factors have had inconsistent associations with ln yield in the literature [17][18][19][20][21][22][23][24] . Nevertheless, although variations in hospital-associated ln yield are larger than those for individual pathologists and surgeons, patient-related variations are largest 18 .…”
Section: Discussionmentioning
confidence: 99%
“…An additional limitation is that adequacy of lymph node harvest can be affected by the reporting pathologist. 12 Our database did not distinguish among reporting pathologists, and adequacy of nodal harvest by pathologist was not available.…”
Section: Strengths and Limitationsmentioning
confidence: 99%